2019
DOI: 10.1016/j.envsoft.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Application of a lower-fidelity surrogate hydraulic model for historic flood reconstruction

Abstract: Two dimensional hydraulic models are useful to reconstruct maximum discharges and uncertainties of historic flood events. Since many model runs are needed to include the effects of uncertain input parameters, a sophisticated 2D model is not applicable due to computational time. Therefore, this papers studies whether a lower-fidelity model can be used instead. The presented methodological framework shows that a 1D-2D coupled model is capable of simulating maximum discharges with high accuracy in only a fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 37 publications
(71 reference statements)
0
40
0
Order By: Relevance
“…Only bed levels of the main channel and floodplains were uncertain caused by the interpolation of the measured cross sections (section 2.2). However, Bomers et al (2019c) found that uncertainties in the floodplain bed levels and main channel bed levels only have a small effect on the maximum discharges throughout the model domain. This justifies to neglect these uncertainties.…”
Section: Setup Of the 1-d/2-d Coupled Modelmentioning
confidence: 88%
“…Only bed levels of the main channel and floodplains were uncertain caused by the interpolation of the measured cross sections (section 2.2). However, Bomers et al (2019c) found that uncertainties in the floodplain bed levels and main channel bed levels only have a small effect on the maximum discharges throughout the model domain. This justifies to neglect these uncertainties.…”
Section: Setup Of the 1-d/2-d Coupled Modelmentioning
confidence: 88%
“…Since the cross sections had an interval of one kilometer, the accuracy near the bifurcation points of the Rhine river branches was not sucient to correctly simulate the discharge partitioning along the Dutch Rhine river branches. Therefore, the DEM at the locations of the bifurcation points is replaced by the 1926 DEM which was available from previous work (Bomers et al, 2019a).…”
Section: Reconstruction Of the 1809 Geometrymentioning
confidence: 99%
“…However, many studies showed the applicability of a 1D-2D coupled model (e.g. Bomers et al 2019a;Domeneghetti et al 2013) and of the diffusive wave equations for flood modelling purposes (e.g. Moya Quiroga et al 2016;Moussa and Bocquillon 2009;Leandro et al 2014).…”
Section: Model Environmentmentioning
confidence: 99%
“…Such inundation patterns are possible in almost any deltaic areas (e.g. Lower Mississippi river and Atchafalaya river (Coleman et al 1998), the Mekong delta (Triet et al 2017) and the Rhine delta (Bomers et al 2018;Klerk et al 2014)).…”
Section: Introductionmentioning
confidence: 99%